The κ-Carbides in Low-Density Fe-Mn-Al-C Steels: A Review on Their Structure, Precipitation and Deformation Mechanism - Peng Chen; Xiaowu Li; Hongliang Yi (Metals, 2020)
Fe-Mn-Al-C steels exhibit an outstanding combination of strength and ductility, and the addition of aluminum drastically reduces the density of steels. The low density also offers the advantage of lightweight structures compared with other alloys in practical applications. The addition of aluminum leads to an increased probability of κ-carbide precipitation, which would significantly affect the mechanical properties. This paper aims to review the κ-carbide in Fe-Mn-Al-C steels, including the structure, elastic and magnetic properties of κ-carbide, the precipitation mechanism of κ-carbide involving thermodynamic equilibrium, and the operative deformation mechanism of κ-carbide that governs the mechanical properties. It is hoped that such a comprehensive summarization of the knowledge of κ-carbide will be beneficial for the further development of low-density Fe-Mn-Al-C steels.